2002
DOI: 10.1046/j.1525-1497.2002.10114.x
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of numerical and statistical differences in abstracts

Abstract: OBJECTIVE:The reporting of relative risk reductions (RRRs) or absolute risk reductions (ARRs) to quantify binary outcomes in trials engenders differing perceptions of therapeutic efficacy, and the merits of P values versus confidence intervals (CIs) are also controversial. We describe the manner in which numerical and statistical difference in treatment outcomes is presented in published abstracts. DESIGN:A descriptive study of abstracts published in 1986 and 1996 in 8 general medical and specialty journals. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…This message is important not only in terms of improving our understanding of the methodological reasons for variability in the framing effects observed between studies but also for physician-patient communication. 13 As well as raising awareness of the potential deficits in the way that clinical trial data presented in the medical literature, drug advertisements, and news media, [14][15][16][17][18][19] this review has highlighted the dangers of providing patients with relative risk reduction information in isolation. It might therefore be argued that to avoid the possibility of misleading patients about the benefits of a treatment, physicians should put the size of the relative changes into perspective by presenting either baseline risk…”
Section: Final Conclusion and Implicationsmentioning
confidence: 99%
“…This message is important not only in terms of improving our understanding of the methodological reasons for variability in the framing effects observed between studies but also for physician-patient communication. 13 As well as raising awareness of the potential deficits in the way that clinical trial data presented in the medical literature, drug advertisements, and news media, [14][15][16][17][18][19] this review has highlighted the dangers of providing patients with relative risk reduction information in isolation. It might therefore be argued that to avoid the possibility of misleading patients about the benefits of a treatment, physicians should put the size of the relative changes into perspective by presenting either baseline risk…”
Section: Final Conclusion and Implicationsmentioning
confidence: 99%
“…6 Another notable finding of our study is that authors commonly report trial results exclusively in relative terms despite a growing recognition that relative risk reporting can distort the magnitude of the effects of an intervention. 13,14,18,19 Given these concerns, readers are likely to be better served by uniform inclusion of absolute risk reporting.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the study did not report whether trials using composite endpoints were more or less likely than trials not using composite endpoints to report significant results. Therefore, it is not clear that these results contradict our finding that trials using composite endpoints are less likely than trials not using composite endpoints to show positive results Disease-Specific Mortality Kip et al 17 An analysis of 20 trials comparing bare metal vs. drug-eluting stents showed that 55% used cardiovascular mortality as an endpoint while 45% used all-cause mortality; another analysis reported in the same paper showed that, among 27 trials published in 2006 in the Journal of the American College of Cardiology, 19% used cardiovascular death as an endpoint while 74% used all-cause mortality Relative Risk Reporting Nuovo et al 14 Fewer than 10% of trials published in top medical journals prior to 1998 reported risk reductions in absolute terms anywhere in the article Dryver et al 18 Among articles published in eight journals in 1996, 12% of the abstracts provided a measure of absolute risk difference; no abstracts published in these journals in 1986 did Schwartz et al 19 Among articles published in 2003 and 2004 in six top journals, 68% of failed to report the underlying absolute risks for the first ratio measure in the abstract and especially since this finding was of borderline significance, the association may represent a chance occurrence. We did not detect other associations between trial funding and endpoint selection or relative risk reporting or between endpoint selection and trial outcomes, however our power to detect some of these associations was limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these data, relative effect measures may be chosen and calculated by readers, researchers, or both and reported along with the absolute measures. 4 …”
Section: Decision Datamentioning
confidence: 99%